Sanctioning Unpermitted Distribution of Pharmacy Preparations: Juridical Review in Ternate City - Selajar, Sophian Yahya; Robo, Basto Daeng; Anshar, Anshar (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This study conducts a juridical review of sanctions imposed on individuals involved in the unauthorized distribution of pharmacy preparations in Ternate City. It aims to evaluate the legal aspects and efficacy of these sanctions in safeguarding public health. Through an analysis of relevant laws, regulations, and judicial precedents, gaps in the existing regulatory framework are identified and suggestions for improvement are proposed. The study assesses the enforcement practices of law enforcement agencies and considers the adequacy and proportionality of the imposed sanctions. Factors such as the seriousness of the offense, potential harm to public health, and the intent of the offenders are taken into account. Challenges pertaining to enforcement capacity, interagency collaboration, and public awareness are also addressed. Based on the findings, recommendations are made to enhance the enforcement of sanctions. These include strengthening collaboration among agencies, providing specialized training for law enforcement personnel, and conducting public education campaigns. The aim is to improve the efficiency and effectiveness of sanction implementation. This research contributes to the field of pharmaceutical law and public health by providing insights for policymakers, regulatory bodies, and law enforcement authorities. The findings inform the development of effective measures to combat the unpermitted distribution of pharmacy preparations.